2021
DOI: 10.3390/cosmetics8010006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Lauryl Sulfate (SLS) Applied as a Patch on Human Skin Physiology and Its Microbiota

Abstract: In this study, we assessed the change in skin microbiota composition, relative abundance, and diversity with skin physiology disruption induced by SLS patch. Healthy women declaring to have a reactive skin were submitted to a 0.5% aqueous sodium lauryl sulfate solution application under occlusive patch condition for 24 h. Skin properties were characterized by tewametry, corneometry, and colorimetry and bacterial diversity was assessed by 16S rRNA sequencing. Analysis before and one day after SLS patch removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
(51 reference statements)
1
20
0
Order By: Relevance
“… 278 , 279 In a clinical trial, the insult of sodium lauryl sulfate, an anionic surfactant, to the stratum corneum was demonstrated by both increased transepidermal water loss (TEWL) and decreased stratum corneum hydration. 324 , 325 Recently, a study showed that detergents cause high TEWL in cleaning personnel due to reduced barrier function, related to the increased risk of work‐related hand dermatitis. 326 Furthermore, it has been observed that with the increased need for hand cleaning during the COVID‐19 pandemic, disinfectants worsen the disease in individuals with a previous history of AD or contact dermatitis and even also cause eczema in healthy individuals.…”
Section: Environmental Substances Affecting the Epithelial Barriersmentioning
confidence: 99%
“… 278 , 279 In a clinical trial, the insult of sodium lauryl sulfate, an anionic surfactant, to the stratum corneum was demonstrated by both increased transepidermal water loss (TEWL) and decreased stratum corneum hydration. 324 , 325 Recently, a study showed that detergents cause high TEWL in cleaning personnel due to reduced barrier function, related to the increased risk of work‐related hand dermatitis. 326 Furthermore, it has been observed that with the increased need for hand cleaning during the COVID‐19 pandemic, disinfectants worsen the disease in individuals with a previous history of AD or contact dermatitis and even also cause eczema in healthy individuals.…”
Section: Environmental Substances Affecting the Epithelial Barriersmentioning
confidence: 99%
“…Direct contact or inhalation of detergents disrupt the epithelial barriers of the skin and respiratory tract, even at very high dilutions or in contact with residues remaining on the laundry after rinsing (7). Surfactants damage the epithelial barrier integrity directly by insulting TJs and related molecules (63,64) facilitating transepidermal water loss, decreasing stratum corneum hydration and inducing Th2 inflammation (63,81). Dietary emulsifiers have been demonstrated to alter the microbiota composition in the gut promoting bacteria with an inflammatory potential and facilitates bacterial penetration though the intestinal mucus layer (82).…”
Section: Environmental Substancesmentioning
confidence: 99%
“…Cosmetics and personal care products are formulated to function as an added nutritional source to the human skin, improve skin barrier functions, inhibit the growth of pathogenic microorganisms, cleanse, and moisturise skin surfaces (Heinrich et al 2014 ; Rodan et al 2016 ; Purnamawati et al 2017 ; Yamaguchi et al 2017 ; Bouslimani et al 2019 ). Despite these health benefits and the subsequent ubiquitous and frequent use of cosmetics and personal skincare products, many of the component ingredients used in their base formulations are often synthesised from petrochemical resources; a key example are surfactants such as synthetic sodium lauryl ether sulphate (SLES), which can make up to 50% (v/v) of the formulation and play a role in emulsification, gelling, and micro-encapsulation (Leoty-Okombi et al 2021 ; Moldes et al 2021 ).These synthetically derived surfactants have drawbacks with regards to their sustainability and are less biodegradable than biologically derived alternatives (Marchant and Banat 2012 ; Suhail et al 2019 ; Goyal and Jerold 2021 ). Synthetically derived surfactants such as SLES are also reported to have the potential to cause allergic reactions, skin irritations, and dysbiosis in the skin microbiome when they come into direct contact with the human skin (Bouslimani et al 2019 ; Mijaljica et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%